2020
DOI: 10.4178/epih.e2020038
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes of quarantine and isolation for infection prevention: A systematic umbrella review of the global evidence

Abstract: METHODS: We searched nine major databases and additional sources and included articles if they were systematically conducted reviews, published as peer-reviewed journal articles, and reported mental health outcomes of quarantine or isolation in any population. RESULTS: Among 1,364 citations, only eight reviews met our criteria. Most of the primary studies in those reviews were conducted in high-income nations and in hospital settings. These articles reported a high burden of mental health problems among patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
375
2
48

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(513 citation statements)
references
References 50 publications
(169 reference statements)
18
375
2
48
Order By: Relevance
“…This difference could be due to the type of immediate health response in the two countries, with clear lockdown measures from the beginning of the pandemic in China [70] and a more fragmented preventive approach in Italy, which may have increased the levels of fears and uncertainty in this country [37][38][39]71]. In fact, the uncertainties about the pandemic progression, the "hypochondriac concerns" [72] and fear that the epidemic is difficult to control represent triggering factors for the development of mental health problems [73,74]. Moreover, studies carried out during natural disasters, war, fires and terroristic attacks found high levels of depressive/anxiety-related symptoms in the general population [75][76][77][78][79][80][81], but nevertheless they were significantly lower compared to those we found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be due to the type of immediate health response in the two countries, with clear lockdown measures from the beginning of the pandemic in China [70] and a more fragmented preventive approach in Italy, which may have increased the levels of fears and uncertainty in this country [37][38][39]71]. In fact, the uncertainties about the pandemic progression, the "hypochondriac concerns" [72] and fear that the epidemic is difficult to control represent triggering factors for the development of mental health problems [73,74]. Moreover, studies carried out during natural disasters, war, fires and terroristic attacks found high levels of depressive/anxiety-related symptoms in the general population [75][76][77][78][79][80][81], but nevertheless they were significantly lower compared to those we found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pregnant women giving birth during the COVID‐19 pandemic represent a high‐risk, vulnerable population that needs to be carefully followed to minimize postpartum mental dysfunction, as previous studies have reported following natural disasters 16 . Medical and mental healthcare interventions should be carried out immediately to prevent deterioration of maternal psychological health, which is made more severe by social containment than reported for previous natural disasters 11 …”
Section: Discussionmentioning
confidence: 99%
“…1 Changes in CES-D-10 scores and in the prevalence of depressive symptoms relative to intergenerational contact frequency. Frequency: 1 = almost never, 2 = less than once a year, 3 = once a year, 4 = once every 6 months, 5 = once every 3 months, 6 = once a month, 7 = every 2 weeks, 8 = once a week, 9 = 2-3 times a week and 10 = almost every day negative psychological impact [52][53][54]. Our findings suggest that children should keep close connections with their older parents during periods of quarantine, which may help reduce the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%